CHARISMATIC LEADERSHIP AND THE SUCCESS TOWARDS SOCIAL WORK OPERATION: A CASE STUDY OF PHRA PHISARN PRACHATHORN VI (PHOB CHOKH TISSAWONGSO), WAT HUAY PLA KANG, CHIANG RAI PROVINCE - Tikhamporn Punluekdej; Lynda Buranachon; Nichapa Leeteerachoti; Phongphan Polyiem; Pinrutai Sutheerapong (Proceedings on Engineering Sciences, 2023)
The results of a research on “Charismatic Leadership and the Success Towards Social Work Operation: A Case Study of Phra Phisarn Prachathorn Vi (Phob Chokh Tissawongso), Wat Huay Pla Kang, Chiang Rai Province” showed that: 1) Wat (temple) Huay Pla Kang is a private monastery under the Maha Nikaya Sangha located in Rim Kok sub-district, Mueang Chiang Rai district, Chiang Rai province with approximately 15 rai in total area having Phra Acharn Phob Chokh as the first abbot of the temple. He has begun his social work about 8 years ago when the villagers brought two orphans under his patronage. 2) The vision and missions performed by Phra Phisarn Prachathorn Vi. regarding the social work operations included: a vision; maintenance of Buddhism, creation of prosperous monastery, continuous cooperation with the community, and helping every walk of life, while the missions are: nothing is much more important than helping people, to be excellent in giving and sharing, and to become a great sacrifice. 3) The characteristics of a charismatic leadership of Phra Phisarn Prachathorn Vi. are:(1)vision, (2)confidence, (3)inspiration, (4) communication, (5) risk taking, and (6) morality and ethics.